Species composition and size distribution of sharks and rays caught in Bali Strait and its surrounding area and its relation to fisheries management - Selvia Oktaviyani; Wanwan Kurniawan; Fahmi Fahmi (Jurnal Iktiologi Indonesia, 2020)
Muncar is one of the shark production centers in Java, where the fishing ground in Bali Strait and its surrounding area. Routine data collection was carried out from May 2018 to April 2019 at the Brak Fish Market and the Muncar Coastal Fishing Port (PPP), Banyuwangi to determine the species composition and size distribution of sharks and rays caught in Bali Strait and its surrounding area. Data collection was done by census and almost of all individuals were identified to species level and and measured. During the study, 3.551 individuals of sharks and rays were landed in this port, consisting of 75 species from 25 families (48 species of sharks, one species of ghost shark and 26 rays species). The most common types of sharks belong to Carcharhinidae and for the rays was Dasyatidae. Among these, thirteen species were listed in Appendix II CITES, i.e. Carcharhinus falciformis, Alopias pelagicus, A. superciliosus, Isurus oxyrhinchus, I. paucus, Sphyrna lewini, S. zygaena, Mobula mobular, M. tarapacana, M. thrustoni, Glaucostegus typus, Rhynchobatus australiae and Rhyna ancylostoma. Most of sharks and rays caught were juvenile to adolescent and at immature or maturing stages. Abstrak Muncar merupakan salah satu sentra produksi hiu di Pulau Jawa dengan daerah tangkapan di perairan Selat Bali dan sekitarnya. Pendataan secara rutin terhadap hasil tangkapan hiu dan pari dilakukan sejak Bulan Mei 2018 hingga April 2019 di Pasar Ikan Brak dan Pelabuhan Perikanan Pantai (PPP) Muncar, Banyuwangi untuk mengetahui kom-posisi spesies dan distribusi ukuran hiu dan pari yang tertangkap dari perairan Selat Bali dan sekitarnya. Pengumpulan data dilakukan secara sensus dan hampir seluruh individu diidentifikasi sampai tingkat spesies serta diukur. Tercatat 3.551 individu hiu dan pari yang didaratkan di wilayah tersebut selama kurun waktu penelitian, yang terdiri atas 75 spesies dan 25 famili (49 spesies hiu dan 26 spesies pari). Spesies hiu yang paling umum ditangkap berasal dari famili Carcharhinidae, sedangkan kelompok pari didominasi oleh famili Dasyatidae. Tercatat ada 13 spesies hiu dan pari Apendiks II CITES yang ditangkap oleh nelayan Muncar, yaitu Carcharhinus falciformis, Alopias pelagicus, A. superciliosus, Isurus oxyrinchus, I. paucus, Sphyrna lewini, S. zygaena, Mobula mobular, M. tarapacana, M. thrustoni, Glaucostegus typus, Rhynchobatus australiae dan Rhina ancylostoma. Sebagian besar hiu dan pari yang ditangkap nelayan berada pada ukuran yuwana hingga remaja, yang belum matang kelamin atau sedang menuju dewasa.